Psychological Foundations of Spiritual and Personal Development of Students in the Structure of Social Mobility - Zavatskyi, Yurii; Toba, Marianna (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the problem of spiritual and personal development of the individual, which is relevant both in science and in social practice. The urgency of this problem is due to reasons of several types: First, the current youth committed to the fullest identify and implement their capacity as seeks to “meet” the modern world as an "equal partner"; secondly, to modern human problem of implementation of all its possibilities connected with quite influential social trends of today derived from “the need for self-actualization”, which has acquired the status of social need and value in modern society. The research shows modern approach to spiritual and personal development of young people. We presented the idea of an integrated approach to nature, mechanisms spiritual and personal development of young people. It was established that the socio-psychological meaning of spiritual and personal development of students is the realization of cognitive-intellectual, sensory, emotional, volitional, creative potential, the implementation of advanced qualitative and quantitative change in the value orientations and actions that result in achieving mental integrity and harmony. We established that this can be interpreted as a form of art, because it is individual knowledge of nature, the discovery of own possibilities and implementation